DETERMINANTS OF ACQUISITION INTEGRATION LEVEL: A DECISION-MAKING PERSPECTIVE. - PABLO, A. L. (Academy of Management Journal, 1994)
Executives of 56 acquiring organizations participated in policy-capturing research that examined how the task, cultural, and political characteristics of acquisitions influence decisions about levels of integration. Although task-related characteristics entered most heavily into managers' decision models, cultural and political factors were also important. These results suggest that an understanding of acquisition integration is best achieved by viewing integration design decisions through multiple theoretical lenses. Furthermore, although industry and acquisition experience explained some variation in integration decision policies, results suggest that other individual or organization-level factors are also at work.